(n+3)*7=56

Simple and best practice solution for (n+3)*7=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n+3)*7=56 equation:


Simplifying
(n + 3) * 7 = 56

Reorder the terms:
(3 + n) * 7 = 56

Reorder the terms for easier multiplication:
7(3 + n) = 56
(3 * 7 + n * 7) = 56
(21 + 7n) = 56

Solving
21 + 7n = 56

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 7n = 56 + -21

Combine like terms: 21 + -21 = 0
0 + 7n = 56 + -21
7n = 56 + -21

Combine like terms: 56 + -21 = 35
7n = 35

Divide each side by '7'.
n = 5

Simplifying
n = 5

See similar equations:

| .02(x-3.99)=1.49 | | 12x^7-12x-11=0 | | (n-5)*4=32 | | (2bc+8b)-(3c-12)= | | 4m-11=45 | | n+5*4=32 | | 10(x+2)=50 | | 20x^2+17x-63=0 | | 9=w-10 | | x^2-16x+5= | | 5x+3=4x+9 | | 7x+2y-21=0 | | 15x+10=6x-5 | | 4x-3y-41=0 | | 9y+2=20 | | X*2+2x-15=0 | | 3x^2-4=12 | | 1y+2=8 | | 72-5x=5x+9 | | v-9=7 | | x=15-1.25y | | x=15-1 | | m-(-3)=10 | | 1x+9=13 | | g+(-7)=9 | | 5x+10=6x-5 | | -25=q-15 | | 0=x+x^2 | | X+0.5x=60 | | 1x+10=6x-5 | | 5x+17=12x-60 | | 2x=48 |

Equations solver categories